Epstein-Barr Virus-Associated T-Cell Lymphoproliferative Disorder Presenting as Chronic Diarrhea and Intestinal Bleeding: A Case Report - Wang, Yaxin; Li, Yajun; Meng, Xiangwei; Duan, Xiumei; Wang, Meilan; Chen, Wenqing; Tang, Tongyu; Li, Yuqin (Frontiers in Immunology, 2018)
Systemic Epstein-Barr virus-positive T-cell lymphoproliferative childhood disease (EBV+T-LPD) is extremely rare. Primary acute or chronic active Epstein-Barr virus infection triggers EBV+T-LPD’s onset and the disease involves clonal proliferation of infected T-cells with activated cytotoxic phenotype. The adult-onset EBV+T-LPD (ASEBV+T-LPD) is even rarer and needs to be extensively studied. Further, according to literature review, it is a challenge to find patients who are immunocompetent and diagnosed with ASEBV+T-LPD involving gastrointestinal tract. This case report discusses a previously healthy middle aged woman who presented with unique symptoms mimicking inflam¬matory bowel disease, and required a total colectomy and terminal ileum rectomy, as reveled by endoscopic examinations, due to severe gastrointestinal bleeding. Post-surgery histopathological findings were confirmatory for the diagnosis of ASEBV+T-LPD (II: Borderline). This patient died 7 months after the diagnosis.